Adult-Onset Neuronal Intranuclear Inclusion Disease: First Korean Case Confirmed by Skin Biopsy - Chun, Min Young; Park, Hee Kyung; Kim, Geon Ha; Lee, Seung-Ah; Kim, Soo-Hyun; Sung, Sun Hee; Park, Yae Won; Jeong, Jee Hyang (Journal of clinical neurology (Seoul, Korea), 2020)
KCI Citation Count: 4